2014
DOI: 10.1158/0008-5472.can-13-2411
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-Sensitive Multimodal Imaging for Detecting Breast Cancer

Abstract: Intraoperative delineation of breast cancer is a significant problem in surgical oncology. A reliable method for demarcation of malignant breast tissue during surgery would reduce the re-excision rate due to positive margins. We present a novel method of identifying breast cancer margins using combined dye-enhanced wide-field fluorescence polarization imaging for en face cancer margins and polarization-sensitive (PS) optical coherence tomography (OCT) for cross-sectional evaluation. Tumor specimens were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…Similarly to previously reported feasibility studies of OCT on breast tissue (26,27,29), the diagnostic accuracy of OCME has not been reported here, as the goal of this study is to establish the contrast provided by OCME in breast tissue. Given the promise of the results presented here, subsequent work will focus on determining the sensitivity and specificity of the presence of malignant tumor in tumor margins.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Similarly to previously reported feasibility studies of OCT on breast tissue (26,27,29), the diagnostic accuracy of OCME has not been reported here, as the goal of this study is to establish the contrast provided by OCME in breast tissue. Given the promise of the results presented here, subsequent work will focus on determining the sensitivity and specificity of the presence of malignant tumor in tumor margins.…”
Section: Discussionmentioning
confidence: 66%
“…A number of studies have evaluated OCT for imaging of excised human breast tissue (26)(27)(28)(29)(30)(31) and lymph nodes (32)(33)(34). These studies have indicated that OCT may be used to visualize breast microarchitecture, but that it is difficult to distinguish tumor from stroma in OCT images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers have demonstrated the reduction of birefringence in tumor tissue in an animal model, and human esophagus, skin, vocal fold, breast and bladder [57,76,156,[162][163][164][165][166][167][168][169][170]. An example of PS-OCT images of a hamster cheek pouch cancer model is shown in Fig.…”
Section: Dermatology Collagen and Nerves Cartilage And The Reduced mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Confocal microscopy is an emerging technology for rapid imaging of freshly excised tissue without the need for frozen-or fixed-section processing. Initial studies have described the major findings of invasive breast cancers using fluorescence confocal microscopy.…”
Section: Introductionmentioning
confidence: 99%